Entering the Contact Zone? Between Colonialism, Neoliberal Resilience and the Possibility of Emancipatory Politics in Puerto Rico’s Post-Maria (Alternautas, 2022)
Undoubtedly, the colonial and neoliberal regime in Puerto Rico precedes the scourge of Hurricane Maria on September 20, 2017. Therefore, when evaluating the “responses” that followed this atmospheric disaster, it is important to consider that the political, legal and economic base for such “answers” have been articulated from a long-standing colonial-neoliberal complex in the island. In this article, the author identifies this complex with what he calls the degenerative evolution of the Commonwealth of Puerto Rico, established in 1952.